2016
DOI: 10.1177/1479164116657304
|View full text |Cite
|
Sign up to set email alerts
|

Tofogliflozin, a selective inhibitor of sodium-glucose cotransporter 2, suppresses renal damage in KKAy/Ta mice, obese and type 2 diabetic animals

Abstract: IntroductionAccording to the Diabetes Atlas, 7th edition, 2015, an estimated 415 million people worldwide had diabetes. 1 Among various vascular complications of diabetes, diabetic nephropathy is a global health challenge because it is a leading cause of end-stage renal disease, which could contribute to the increased risk of cardiovascular disease and death in diabetic patients. 2 Recently, inhibitors of sodium-glucose cotransporter 2 (SGLT2) have been developed as a novel oral hypoglycaemic agent. 2 Since 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…According to the plasma Tofo concentrations in mice and in humans, the 0.015% Tofo dose given to the KK‐A y mice in this study is comparable to the therapeutic dose of 20 mg for patients with type 2 diabetes (Ishibashi et al. ). The animal care and experimental procedures were approved by the Animal Care Committee of Tokyo New Drug Research Laboratories, Kowa Company.…”
Section: Methodssupporting
confidence: 52%
“…According to the plasma Tofo concentrations in mice and in humans, the 0.015% Tofo dose given to the KK‐A y mice in this study is comparable to the therapeutic dose of 20 mg for patients with type 2 diabetes (Ishibashi et al. ). The animal care and experimental procedures were approved by the Animal Care Committee of Tokyo New Drug Research Laboratories, Kowa Company.…”
Section: Methodssupporting
confidence: 52%
“…Interestingly, drugs that tightly regulate glucose have unexpectedly shown cardiovascular and renal benefit in clinical trials and in rodent models of nephropathy in obese and type 2 diabetic animals: Those drugs that target glucose transporters, such as the sodium glucose cotransporter 2 (SGLT2) inhibitors, empagliflozin and canagliflozin, slow renal decline, independent of their effects on glycemia. 76 79 A recent study investigating possible mechanisms of renoprotection showed that SGLT2 inhibitors decrease TSP1 expression in two human proximal tubular cell lines. 80…”
Section: Tsp1 As An Activator Of Latent Tgf-β In Renal Fibrosismentioning
confidence: 99%
“…We have previously shown that (1) engagement of RAGE with glycer-AGEs evokes inflammatory, thrombogenic, and fibrotic reactions in human renal proximal tubular cells via ROS generation, (2) sodium-glucose cotransporter 2 (SGLT2)-mediated, high glucose-induced ROS generation augments the glycer-AGE-induced apoptotic cell death of proximal tubular cells via RAGE induction, and (3) inhibitors of SGLT2, such as empagliflozin and tofogliflozin, protect against proximal tubular injury in diabetic animals through its anti-oxidative, anti-inflammatory and anti-fibrotic properties via inhibition of the glycer-AGE-RAGE axis [6,[13][14][15][16]. Furthermore, recently, high glucose or AGEs have been shown to promote human renal proximal tubular epithelial cell migration and epithelial-to-mesenchymal transition via oxidative stress generation, all of which were ameliorated by empagliflozin [17].…”
Section: Discussionmentioning
confidence: 99%